Yahoo Web Search

  1. Ads
    related to K.C
  1. Sort by

  1. ...and h. You can see the latter as follows: f(x) = c . a^(d(x-h)) + k = c . a^(dx) . a^(-dh) + k = c' . a^(dx) + k, where c' = c . a^(-dh) So we...

    2 Answers · Science & Mathematics · 06/04/2016

  2. ...prime, we may conclude that p|m. Writing m = cp for some integer c, we get (cp)^k = c^k * p^k = p * n^k ==> n^k = c^k * p^(k-1). Since k > 1, we have...

    1 Answers · Science & Mathematics · 14/10/2009

  3. ...the constant. We know that initially, v(0) = 0, so: 0 = C - g*M/k C = g*M/k v(t) = (g*M/k)*(exp(-k*t/M) - 1) Now, v...

    1 Answers · Science & Mathematics · 28/03/2010

  4. ...the constant. We know that initially, v(0) = 0, so: 0 = C - g*M/k C = g*M/k v(t) = (g*M/k)*(exp(-k*t/M) - 1) Now, v...

    1 Answers · Science & Mathematics · 28/03/2010

  5. ...the constant. We know that initially, v(0) = 0, so: 0 = C - g*M/k C = g*M/k v(t) = (g*M/k)*(exp(-k*t/M) - 1) Now, v...

    1 Answers · Science & Mathematics · 28/03/2010

  6. ...the constant. We know that initially, v(0) = 0, so: 0 = C - g*M/k C = g*M/k v(t) = (g*M/k)*(exp(-k*t/M) - 1) Now, v...

    2 Answers · Science & Mathematics · 29/03/2010

  7. ...the constant. We know that initially, v(0) = 0, so: 0 = C - g*M/k C = g*M/k v(t) = (g*M/k)*(exp(-k*t/M) - 1) Now, v...

    2 Answers · Science & Mathematics · 29/03/2010

  8. ...of the result ln (T - 21) = kt + C ..........................(1) ln (26 - 21) = 5*k + C = ln(5) ln (41 - 21) = 0*k + C = ln 20 ...........(2) 5k = ln(5) - ln(20) = ln(1...

    3 Answers · Science & Mathematics · 30/03/2013

  9. ...) = C/A*k/A - C/B*k/B = C*k - C*k = 0 So now we only have to show that if we start at point (x1,y1) and then...

    1 Answers · Science & Mathematics · 19/09/2009

  10. hypergeometric distribution. use combinations sum C(12,k)*C(88,25-k)/C(100,25), k = 3 to 5 = .5786 <-----

    2 Answers · Science & Mathematics · 08/03/2014

  1. Ads
    related to K.C
  1. Try asking your question on Yahoo Answers